Characterisation and heterologous biosynthesis of burnettiene A, a new polyene-decalin polyketide from Aspergillus burnettii. Issue 43 (29th October 2021) - Roux, Indra; Bowles, Simon; Kalaitzis, John A.; Vuong, Daniel; Lacey, Ernest; Chooi, Yit-Heng; Piggott, Andrew M.
Abstract : Burnettiene A is a novel cytotoxic tridecaketide decalin polyketide from Aspergillus burnettii . Its biosynthesis was elucidated by heterologous expression in fungi. Abstract : Chemical exploration of the recently described Australian fungus, Aspergillus burnettii, uncovered a new metabolite, burnettiene A. Here, we characterise the structure of burnettiene A as a polyene-decalin polyketide. Bioinformatic analysis of the genome of A. burnettii identified a putative biosynthetic gene cluster for burnettiene A ( bue ), consisting of eight genes and sharing similarity to the fusarielin gene cluster. Introduction of the reassembled bue gene cluster into Aspergillus nidulans for heterologous expression resulted in the production of burnettiene A under native promoters. Omission of bueE encoding a cytochrome P450 led to the production of preburnettiene A, confirming that BueE is responsible for catalysing the regiospecific multi-oxidation of terminal methyl groups to carboxylic acids. Similarly, bueF was shown to encode an ester-forming methyltransferase, with its omission resulting in the production of the tricarboxylic acid, preburnettiene B. Introduction of an additional copy of the transcription factor bueR under the regulation of the gpdA promoter significantly improved the heterologous production of the burnettienes. Burnettiene A displayed strong in vitro cytotoxicity against mouse myeloma NS-1 cells (MIC 0.8 μg mL −1 ).